2017
DOI: 10.1002/slct.201701423
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Hydrogenation of Unsaturated Substrates by Half-sandwich Ruthenium Catalysts using Ammonium Formate as Reducing Reagent

Abstract: A series of half‐sandwich phosphine‐ and NHC‐supported complexes were screened in catalytic transfer hydrogenation of nitriles, N‐heterocycles, olefins, and carbonyls by using ammonium formate as the reductant. Complex [Cp(iPr3P)Ru(NCCH3)2][PF6] (3) was found to be the most efficient catalyst. Mechanistic studies suggested that the formate complexes Cp(iPr3P)Ru(κ2‐O2CH) and Cp(iPr3P)Ru(κ1‐O2CH)(NCCH3) could be the true catalysts in these reactions. An inner‐sphere monohydride mechanism was suggested. Excess fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Tremendous interest toward the development of a wide range of stable cyclopentadienyl–Ru­(II) (η 5 -Cp–Ru) complexes has been observed over the past five decades. , Consequently, due to the unique structural properties, stability, and chemical reactivity of the η 5 -Cp–Ru­(II) complexes, these complexes find application in various fields (Scheme ), including small-molecule activation, transfer hydrogenation, and biology. In the particular context of catalysis, one of the prominent η 5 -Cp–Ru­(II)-based transfer hydrogenation catalysts is Shvo’s catalyst, which demonstrated the involvement of both the metal and the ligand to control the selectivity. , Nikonov’s group also demonstrated the application of [(η 5 -C 5 H 5 )­Ru­( i Pr 3 P)­(NCCH 3 ) 2 ] in the transfer hydrogenation of ketones, nitriles, esters, and N-heterocycles. , Studies demonstrated the formation of (η 5 -C 5 H 5 )­Ru–H (ruthenium hydride) as an important intermediate species, which facilitated the transfer hydrogenation of these unsaturated groups. Moreover, mechanistic studies by NMR also revealed the presence of the trihydride species [(η 5 -C 5 H 5 )­Ru­(NHC)­(H) 3 ] (NHC is a carbene ligand) as the catalyst resting stage for the transfer hydrogenation reaction . Weissensteiner et al also demonstrated the catalytic reactivity of the η 5 -Cp–Ru­(II) aminophosphine (PN) complexes [(η 5 -C 5 H 5 )­Ru­(κ 2 -PN)­CH 3 CN] + and [(η 5 -C 5 H 5 )­Ru­(κ 2 -PN)­Br] for the transfer hydrogenation of a wide range of ketones to secondary alcohols .…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous interest toward the development of a wide range of stable cyclopentadienyl–Ru­(II) (η 5 -Cp–Ru) complexes has been observed over the past five decades. , Consequently, due to the unique structural properties, stability, and chemical reactivity of the η 5 -Cp–Ru­(II) complexes, these complexes find application in various fields (Scheme ), including small-molecule activation, transfer hydrogenation, and biology. In the particular context of catalysis, one of the prominent η 5 -Cp–Ru­(II)-based transfer hydrogenation catalysts is Shvo’s catalyst, which demonstrated the involvement of both the metal and the ligand to control the selectivity. , Nikonov’s group also demonstrated the application of [(η 5 -C 5 H 5 )­Ru­( i Pr 3 P)­(NCCH 3 ) 2 ] in the transfer hydrogenation of ketones, nitriles, esters, and N-heterocycles. , Studies demonstrated the formation of (η 5 -C 5 H 5 )­Ru–H (ruthenium hydride) as an important intermediate species, which facilitated the transfer hydrogenation of these unsaturated groups. Moreover, mechanistic studies by NMR also revealed the presence of the trihydride species [(η 5 -C 5 H 5 )­Ru­(NHC)­(H) 3 ] (NHC is a carbene ligand) as the catalyst resting stage for the transfer hydrogenation reaction . Weissensteiner et al also demonstrated the catalytic reactivity of the η 5 -Cp–Ru­(II) aminophosphine (PN) complexes [(η 5 -C 5 H 5 )­Ru­(κ 2 -PN)­CH 3 CN] + and [(η 5 -C 5 H 5 )­Ru­(κ 2 -PN)­Br] for the transfer hydrogenation of a wide range of ketones to secondary alcohols .…”
Section: Introductionmentioning
confidence: 99%
“…In acetonitrile, the reaction did not form methane or methyl iodide, and only methanol as well as unidentified peaks were detected (Table 1, entry 9), which may arise from the decomposition of acetonitrile. 66 In DMF-d 7 , methane was formed in 73% yield, albeit together with 24% of methanol after 3 days of reaction (Table 1, entry 10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The influence of the solvent was then tested: replacing THF with an apolar solvent, benzene- d 6 , led to a very low (12%) conversion, and mostly methyl iodide was observed (Table , entry 8). In acetonitrile, the reaction did not form methane or methyl iodide, and only methanol as well as unidentified peaks were detected (Table , entry 9), which may arise from the decomposition of acetonitrile . In DMF- d 7 , methane was formed in 73% yield, albeit together with 24% of methanol after 3 days of reaction (Table , entry 10).…”
Section: Resultsmentioning
confidence: 99%
“…In acetonitrile, the reaction did not form methane or methyl iodide, and only methanol as well as unidentified peaks were detected (Table 1, Entry 9), which may arise from the decomposition of acetonitrile. 23 In DMF-d7, methane was formed in 73 %yield, albeit together with 24 % of methanol after three days of reaction (Table 1, Entry 10).…”
Section: Resultsmentioning
confidence: 99%